BAYESIAN NETS AS MODELLING IN PSYCHOLOGY - López Puga, Jorge; García García, Juan; De la Fuente Sánchez, Leticia; De la Fuente Solana, Emilia Inmaculada (Anales de Psicología / Annals of Psychology, 2007)
Bayesian Nets as Modelling Tools in Psychology.Abstract: There is more and more research projects which have a lot of variables with complex relations between them. Bayes nets are statistical tools emerged from Artificial Intelligence field that allow us to face up these research situations. A Bayes net is a directed acyclic graph that repre-sents conditional dependence and independence probabilistic relations and it uses the Bayes rule to update the model when some evidences are took into account. The paper describes Bayes nets mathematical essentials and the advantages as opposed to others multivariate tools. Finally, we review applications and potential applications of Bayes nets in Psychology.